Recent developments in automatic control systems - Kondratenko, Yuriy P. (River Publishers series in automation, control and robotics., 2021)
The monograph provides an overview of the recent developments in modern control systems including new theoretical finding and successful examples of practical implementation of the control theory in different areas of industrial and special applications. Recent Developments in Automatic Control Systems consists of extended versions of the selected papers presented at XXVI International Conference on Automatic Control "Automation 2020" (October 13-15, 2020, Kyiv, Ukraine) which is the main Ukrainian Control Conference organized by Ukrainian Association on Automatic Control (National member organization of IFAC) and National Technical University of Ukraine «Igor Sikorsky Kyiv Polytechnic Institute». This is a third monograph in the River Publishers series in Automation, Control and Robotics, which is publishing based on the selected papers of the Ukrainian Control Conferences "Automation", in particular, first monograph "Control Systems: Theory and Applications (2018) was published based on the "Automation - 2017" and second monograph "Advanced Control Systems: Theory and Applications" - based on the "Automation - 2018". The monograph is divided into three main parts: (a) Advances in Theoretical Research of Control Systems; (b) Advances in Control Systems Application; (c) Recent Developments in Collaborative Automation. The chapters have been structured to provide an easy-to-follow introduction to the topics that are addressed, including the most relevant references, so that anyone interested in this field can get started in the area. This book may be useful for researchers and students who are interesting in recent developments of the modern control systems, robust adaptive systems, optimal control, fuzzy control, motion control, identification, modelling, differential games, evolutionary optimization, reliability control, security control, intelligent robotics and cyber-physical systems.